Effectiveness of Educational Videos and Personal Hygiene Counseling in Prevention of Skin Diseases on Students' Knowledge and Attitudes at Jati Sanan Islamic Boarding School - Rochmah Fidhiniyah, Nur; Riza Yuliawati (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
Skin disease is a common disease in all members of society. In Jati Sanan Islamic Boarding School, there are 45 students who have experienced redness of the skin, 44 students who have experienced itching, 28 students have experienced skin that feels like it is burning, 32 students have experienced hives, 29 have experienced white/red spots accompanied by itching, and 33 students have experienced repeated skin complaints. Factors that influence the occurrence of skin disease in students are suspected to be environmental factors and individual behavior of the students themselves are still lacking. This study is to analyze the differences in knowledge and attitudes of students before and after being given counseling on preventing skin diseases at the Jati Sanan Islamic Boarding School. Method: In this study, the researcher usedexperimental research type with Pre-Experimental Designs form. The research design is One Group Pretest-Posttest Research Design. This research design combines Pretest and Posttest Study. With a sample of 101 students at the Jati Sanan Islamic Boarding School. The value of knowledge and attitudes of students before and after the provision of counseling increased. The results of the analysis showed a p-value of 0.00 <0.05, meaning that it can be concluded that there is a difference in knowledge and attitudes before and after the provision of counseling to students. The importance of learning using video media combined with PPT provides benefits that can increase students' knowledge in understanding efforts to prevent skin diseases.